Bond on NSM CFRP systems: recent contributions of UMinho on durability, quality control and design - Sena-Cruz, José (2016)
In the last years, significant research in the context of bond of near-surface mounted (NSM) fibre reinforced polymer (FRP) systems in concrete has been conducted at the Department of Civil Engineering of the University of Minho. This paper presents a brief summary of the major results obtained in that research, namely in terms of durability, quality control and design topics. Accelerated ageing tests on NSM FRP bond specimens were conducted to simulate different environmental conditions. A new method was developed and applied to investigate the evolution of the adhesive stiffness and the bond behaviour of NSM systems for different curing conditions used for quality control of FRP installations. Regarding the bond design, two existing guidelines’ formulas were adapted to the partial safety factors framework.